Efektivitas Pengelolaan Badan Usaha Milik Desa Dalam Meningkatkan Pendapatan Desa Di Desa Cunca Lolos Kecamatan Mbeliling Kabupaten Manggarai Barat - Candra, Margaretha Shintya; Mahur, Agustinus; Asnawi, Norani (Law Faculty, Nusa Cendana University, 2023)
The village owned enterprise agency (BUMDes) was established in accordance with the needs and potential of the village. The establishment of a village owned enterprise agency (BUMDes) can be one of the strategies that should be considered in the effort to build a village. Operational BUMDes can provide profits and add revenue to the village’s finances. Currently, Bantang Cama village enterprise agency in Cunca Lolos village has not been operated effectively because its role in increasing the income of the village is not clearly seen. The problem formula in this study is: (1) How efficient is the management of the village owned enterprise agency in increasing the village income? (2) What are the factors that hinder the management of the village owned enterprise agency in increasing the village income? This research is empirical and is descriptive and analyses primary data to determine the effectiveness of the management of the village owned enterprise agency increasing the village income. Data collection using interviews, observations and documentation techniques. The results of this research show that: (1) The management of BUMDes Bantang Cama Village Cunca Lolos is not effective and (2) The impeding factors include the limited human resources of managers, the lack of incentives for the manager, the support of the public is not maximum, the transparency and accountability of the managers BUMDes is very low.